PREDIKSI KEBANGKRUTAN CV. BATUBARA MAS ABADI DI SAMARINDA - -, Lisa Cinthia (EKONOMIA, 2014)
The company was founded with the hope of generating a profit to be able to survive in the long term infinite. The company uses profits generated to develop and maintain the continuity of the company. Often companies that have been operating for a certain period forced to disband because of a business failure. One way to do company for the company to survive, by interpreting or analyzing financial statements. The problem in this study is "Is the CV. Batubara Mas Abadi in Samarinda potentially bankrupt in 2010, 2011, 2012, and 2013? ". The purpose of this study to determine the potential bankruptcy using the Altman Z-Score in CV. Batubara Mas Abadi. By hypothesis "CV. Batubara Mas Abadi is not potentially bankrupt in 2010, 2011, 2012, and 2013. "Analytical tool used to determine the potential bankruptcy of this research is the Altman Z-Score models. From the analysis and discussion, it can be concluded seen from 2010 to 2013 CV. Batubara Mas Abadi in Samarinda in healthy financial condition and not potential to be bankrupt, It is evidenced from the results of the value of Zi in 2010 at 4,5090, in 2011 at 4,6484, in 2012 at 5,0892, in 2013 at 5,6963, which means that the value of Zi in the year 2010 to 2013 more than 2,90. Where if the value of Zi is more than 2,90 that enterprise companies are categorized as healthy financial condition and not potential to be bankrupt.